ASSESSMENT OF ELECTROMAGNETIC FIELDS (EMF) ON HUMAN HEALTH IN UYO METROPOLIS - Dr. Mfreke Umoh J.; Ekpo, Edet George; Ekpa, Andikan Kenneth (International Journal of Innovations in Engineering Research and Technology, 2022)
The society have been overwhelmed by the expanding sources of Electromagnetic Field (EMF) that come from communications, electricity, appliances, medical equipment, and many more things that we use in our everyday lives since the beginning of the twentieth century. Despite the fact that these new technologies have become unavoidable and vital, the electromagnetic fields they generate may pose health concerns and dangers to humans. Some studies have shown a relationship between EMF exposure and an increased risk of leukaemia, cancer, brain tumours, and other illnesses. Furthermore, there is substantial ambiguity about the exact processes causing these biological dangers, as well as whether types of magnetic, electric, or both fields are of major concern. It goes without saying that, regardless of whether the consequences of this EMF are minor or severe, the study recommends that we take all reasonable steps to keep our exposure to EMF to a minimum. To achieve this, all parties participating in or impacted by the exposure should adhere to the RF safety regulations and recommendations established by regulatory bodies such as the IEEE, WHO, ICNIRP, and other similar organisations. If the aforementioned instructions are not followed immediately, the population will be exposed to a high pandemic risk of possibly lethal illnesses in the future.